If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 9) = 2x + -1 Reorder the terms: 4(9 + x) = 2x + -1 (9 * 4 + x * 4) = 2x + -1 (36 + 4x) = 2x + -1 Reorder the terms: 36 + 4x = -1 + 2x Solving 36 + 4x = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 36 + 4x + -2x = -1 + 2x + -2x Combine like terms: 4x + -2x = 2x 36 + 2x = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 36 + 2x = -1 + 0 36 + 2x = -1 Add '-36' to each side of the equation. 36 + -36 + 2x = -1 + -36 Combine like terms: 36 + -36 = 0 0 + 2x = -1 + -36 2x = -1 + -36 Combine like terms: -1 + -36 = -37 2x = -37 Divide each side by '2'. x = -18.5 Simplifying x = -18.5
| -8x+4(1+5x)=-6-1 | | .19x+.33=2.04 | | w*6/e=36 | | -2x+39=x+18 | | 3(x-2)=35.7 | | x^2+y^2-8x-4y+3=0 | | -2x-12=-5x-3 | | -3.9x=-11.31 | | 34/50 | | X+3.9=-8.7 | | sqrt(x+1)-2=sqrt(x+3)+x | | 5X+X+y+(y+29)=127 | | 3y+3x=0 | | 3n^2+37n-1360=0 | | 6(s-2)=5(s+10) | | 144=18n+45 | | 14+2(4s-3)=40 | | 3n-7=6n-2n | | 3/9=y/21 | | (8x+100)+(2x+50)=90 | | 6x-7/7x=6=x-3/x-2 | | 5y=4cosx+1 | | 4-7z=22+22 | | 8a^3-27= | | 4s+4t= | | 6x-17=2x+3 | | 8(x-3)=-7(x+2)+47 | | r-1=4+6r | | 32+8x=38+7x | | x*x+7x=11 | | 3x^(1/2)-13x^(1/4)-30=0 | | 0=16t^2+60t+4 |